Determinants Of Capital Market Development In Ghana - Acquah-Sam, Emmanuel (European Scientific Journal, ESJ, 2016)
This study sought to investigate the macroeconomic factors that influence capital market development in Ghana. The study was based on multiple linear regression analysis based on quarterly secondary data spanning from 1991 to 2011. Exploratory data analysis was used to verify and resolve basic assumptions of multivariate analysis. Research tools such as Principal Component Analysis (PCA), Structural Equation Modelling (SEM) through Path Analysis (i.e. Layered Regression technique) and tests of interactions among variables were used to test for the linear relationships between key variables in the estimated equations. The main empirical contribution of this study is that capital market development in Ghana is positively influenced by gross capital formation (GFI) and GDP growth, but negatively influenced by Treasury bill rates (T-BILLS). Inflation and foreign direct investments (FDI) did not prove significant in the estimated equation. These imply that policy-makers in Ghana should promote the growth of real income or output, and physical infrastructural development to enhance capital market development in Ghana. Interest rates and the government of Ghana’s Treasury bill rates must be fixed at reasonable levels to encourage investments in capital market securities. The application of this study is that the results and the estimated model are useful for predicting long run growth paths of capital markets in developing countries when country specific problems are well addressed.